Systemic crises and growth - Rancière, Romain; Tornell, Aaron; Westermann, Frank 1970- (National Bureau of Economic Research, 2005)
"In this paper, we document the fact that countries that have experienced occasional financial crises have, on average, grown faster than countries with stable financial conditions. We measure the incidence of crisis with the skewness of credit growth, and find that it has a robust negative effect on GDP growth. This link coexists with the negative link between variance and growth typically found in the literature. To explain the link between crises and growth we present a model where weak institutions lead to severe financial constraints and low growth. Financial liberalization policies that facilitate risk-taking increase leverage and investment. This leads to higher growth, but also to a greater incidence of crises. Conditions are established under which the costs of crises are outweighed by the benefits of higher growth"--National Bureau of Economic Research web site.
Keywords: Wirtschaftsentwicklung; Ökonometrisches Modell; Depressions; Economic development -- Econometric models